Peran Generasi Milenial Terhadap Pemahaman dan Perkembangan Fintech syariah - Muhammad Adam; Marliyah Marliyah (Universitas Islam Sumatera Utara, 2022)
The rapid development of technology has made all sectors influential, namely the education sector, industry, as well as the economic, financial and banking sectors. One of the links between the millennial generation and the development of fintech is because the millennial generation is a technology literate generation that is able to accept financial technology innovations. Financial technology (fintech) or what we usually know as online loans (financial loans) are no longer foreign to the public. Apart from operating in the conventional sector, there is also sharia fintech. Safe and lawful money loans because they operate based on Islamic law. This study aims to determine the role of the millennial generation in understanding and developing sharia fintech in increasing economic growth. This research method uses inductive, then analyzed and then presented in writing in the form of reports in the form of data found from interviews and documentation.